The total quality corporation : - McInerney, Francis (Truman Talley Books, 1995)
McInerney and White (Beating Japan) set out to disprove the perception that pollution control is bad for business by tracing the increase in profitability of 10 corporations that took steps to reduce waste. A Nissan car-manufacturing plant in Tennessee eliminated disposable containers from its production process, reducing the amount of its garbage from 20 dumpster loads a day to only one, and developed a paint process that no longer sends solvents into the air. Exxon, saddled with an image problem after the Valdez oil spill in Alaska, began a waste-control program that takes by-products from its refineries and converts them to other uses. Buena Vista Wineries in California switched to organic farming methods. As the authors argue, biodegradable trash bags and compostable diapers are no longer enough; the challenge now is to fuse the desire for a clean environment and desire for profit.